Integrating Animal Husbandry With Crops and Trees - Lal, Rattan (Frontiers in Sustainable Food Systems, 2020)
Per capita intake of animal protein is expected to increase globally through 2050, and the rate of increase will be more in emerging economies than that in developed countries. Global meat consumption between 1980 and 2050 is projected to increase from 133 million to 452 million tonnes, of which 86% (279 million tonnes) of the global increase will occur in developing countries. Animal-based agricultural systems occupy 45% of the global land area and contribute 18% of anthropogenic emissions. In addition to being a major source of nitrous oxide (N2O), methane (CH4) and other greenhouse gases (GHGs), livestock also use 8% of the global water withdrawal. The animal sector is dominated by resource-poor and small landholders of developing countries. Adverse effects of livestock on the environment are caused by the way animal husbandry is practiced, and animals are not integrated with other agricultural and forestry-based practices. Thus, improving and sustaining the livestock sector is critical to advancing the Sustainable Development Goals (SDGs) of the United Nations, especially SDG #1 (No Poverty), SDG #2 (Zero Hunger), SDG #6 (Clean Water and Sanitation), and SDG #13 (Climate Action). Separation of the raising of livestock from that of the cultivation of seasonal crops and perennial trees has decoupled the biogeochemical/biogeophysical cycling of carbon (C), water (H2O), nitrogen (N), phosphorus (P), and sulfur (S). This decoupling is a causative factor of the increase in emissions of N2O and CH4, eutrophication and contamination of water resources, degradation of rangelands, and decline in its biodiversity. Therefore, identification and a widespread adoption of integrated systems of livestock with that of crops and trees are critical to reduce the environmental footprint of animal-based dietary products. Incorporation of pastures/forages in the rotation cycle along with controlled grazing, called ley farming, and agroforestry, such as alley cropping, are examples of integrated farming systems. Other strategies of reducing the environmental footprint comprise the following: reducing enteric fermentation by precision feeding and matching dietary protein to animal need, processing CH4 and N2O emissions for other uses, and managing manure and other animal waste prudently. Other considerations include multiple GHG perspectives and SOC sequestration.